Stability Analysis and Yield Evaluation on Some Lowland Rice Genotypesin Nigeria - Bashir, M. N.; Isong, A.; Aliyu, U.; Bakare, S. O.; Ehirim, B. O.; Onotugoma, E.; Shema, A. M.; Mohammed, I. G.; Adagba, M. N.; Gbadeyan, S. T.; Aremu, P. A.; Mummen, A. Y. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Improved genotypes can contribute immensely to productivity of high yielding varieties when they are released mainly in the ideal and adapted environments. To enhance adoption and sustainable production of new improved lowland rice genotypes in Nigeria, yield evaluation,analysis of stability models on seven (7) lowland rice genotypes (ARS 161-3-5-5-3-B-BD, ARS 563-14-B-ED, ARS 150-TGR-10-NCRIB-12, ART 64-26-1-1-B-B-ED, D 56-NCRI J-1-1, ART 90–46-1-1-B-B-ED and ART 739-2-6-B-BD) and two national checks (FARO 44 and FARO 57) in 2020 and 2021 for nine (9) environments were under taken. The design was randomized complete block having three replicates. AMMI and GGE Biplot analyses were adopted to identify stable and adaptable genotypes across the environments. The stability as recommended by FINLAY-WILKINSON indicated that genotypes ART 739-2-6-B-BD, ART 90–46-1-1-B-B-ED and ARS 150-TGR-10-NCRIB-12 expressed 21%, 19% and 24% respectively less than 1 in slope for the combined two years analysis. AMMI analysis partitioned the environment into 8 principal components, the variances at all the principal components recorded high but not significant difference at 5% probability except Principal Component 1. This thereforeimplies that principal component 1 has substantive variances that can be exploited. Principal Component PC1, PC2 and PC3 accounted for 99.70% of AMMI experimental variance and ARS 161-3-5-5-3-B-BD as measured by principal components suggested to be not only high yielding, more stable, but also more ideal in all the tested environments